2010
DOI: 10.1074/jbc.m110.138206
|View full text |Cite
|
Sign up to set email alerts
|

Rad18-mediated Translesion Synthesis of Bulky DNA Adducts Is Coupled to Activation of the Fanconi Anemia DNA Repair Pathway

Abstract: Fanconi anemia (FA) is a cancer susceptibility syndrome characterized by sensitivity to DNA-damaging agents. The FA proteins (FANCs) are implicated in DNA repair, although the precise mechanisms by which FANCs process DNA lesions are not fully understood. An epistatic relationship between the FA pathway and translesion synthesis (TLS, a post-replication DNA repair mechanism) has been suggested, but the basis for crosstalk between the FA and TLS pathways is poorly understood. We show here that ectopic overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
72
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 46 publications
5
72
0
Order By: Relevance
“…In response to bulky DNA lesions, Rad18-dependent FA pathway activation is mediated via PCNA ubiquitylation and requires Polη. 27 We show here that in contrast with bulky DNA lesions, CPT does not induce PCNA ubiquitination. Surprisingly, however, we demonstrate that Rad18-mediated FA pathway activation by CPT and tolerance of CPT-induced damage are dependent on Rad18 E3 ubiquitin ligase activity.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…In response to bulky DNA lesions, Rad18-dependent FA pathway activation is mediated via PCNA ubiquitylation and requires Polη. 27 We show here that in contrast with bulky DNA lesions, CPT does not induce PCNA ubiquitination. Surprisingly, however, we demonstrate that Rad18-mediated FA pathway activation by CPT and tolerance of CPT-induced damage are dependent on Rad18 E3 ubiquitin ligase activity.…”
mentioning
confidence: 56%
“…Indeed, deficiency or mutations in multiple components of the FA pathway (FANCB, FANCM, FANCJ, FANCD1, FANCD2 and FANCI) leads to CPT sensitivity. 36,[38][39][40] However, little is known regarding activation mechanisms of the FA pathway and its role in response to Top1-inhibitors-induced DNA damage.Because we and others recently showed that Rad18 contributes to FA pathway activation in response to bulky DNA adducts, 27 it was of interest to test the potential role (if any) of Rad18 in CPT-induced FA pathway activation. In response to bulky DNA lesions, Rad18-dependent FA pathway activation is mediated via PCNA ubiquitylation and requires Polη.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[122][123][124][125][126] RAD18-RAD6 catalyzes the monoubiquitination of PCNA on K164, a molecular event necessary for DNA polymerase switching during translesion DNA synthesis (TLS).…”
Section: Fancd2 and Fanci Functionmentioning
confidence: 99%
“…122,126 Genetic disruption of RAD18 or RAD18 depletion via siRNA leads to decreased ICL-induced FANCD2/I monoubiquitination and chromatin binding. [122][123][124][125][126] Furthermore, RAD18-RAD6 mediated monoubiquitination of PCNA on K164 is necessary for efficient FANCD2 monoubiquitination. 122 FANCL was also shown to bind to PCNA directly and PCNA K164 monoubiquitination was shown to be required for FANCL chromatin loading.…”
mentioning
confidence: 99%